The National SOM Survey 1990 - SOM Institute, University of Gothenburg (University of Gothenburg, 1992)
The questionnaire for the fifth study in the series of annual SOM-surveys was divided into seven subject fields: mass media; politics and society; energy, nuclear power and environment; Sweden´s relation to other countries; Islam; leisure; and background. The SOM surveys contains a core of questions asked annually. New questions in SOM90 dealt with good qualities in daily papers; priority of news from different areas; confidence in Swedish mass media; whether different activities should be handled by the public sector or by private enterprises, associations, or by individuals; government intervention; opinions on different suggestions in the Swedish environmental debate, and own environmental activities; attitudes toward Islam.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den femte undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1990 års undersökning består av sju sammanhållna delar: massmedier; politik och samhälle; energi, kärnkraft och miljö; Sveriges förhållande till omvärlden; islam; fritid; samt bakgrundsuppgifter.

Många av frågorna har ställts i tidigare SOM-undersökning, men ett antal frågor har tillkommit. Nya frågeställningar i Riks-SOM 1990 gäller viktiga egenskaper hos en dagstidning; prioritering av nyheter från olika områden; förtroende för de svenska massmedierna; huruvida olika verksamheter bör skötas av stat och kommun eller av privata företag, föreningar eller enskilda; statens styrning av kommuner, näringsliv och enskilda; åsikter om olika förslag i den svenska miljödebatten, samt egna miljöaktiviteter; och inställning till islam.

Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1990
Riks-SOM 1990
Keywords: elections; val; mass media; massmedia; population migration; migration; defence; försvar; participation; deltagande; public sector; offentlig sektor; ethics; etik; international relations; internationella relationer; energy; energi; environment; miljö; leisure time; fritid; trust; förtroende; quality of life; livskvalitet; political interest; politiskt intresse; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; membership; medlemskap; state control; statlig styrning; news; nyheter; television news; tv-nyheter; television programmes; tv-program; radioactive wastes; radioaktivt avfall; equipment; utrustning; local press; lokalpress; privatization; privatisering; economic conditions; ekonomiska villkor; risk; risk; islam; islam; internal politics; inrikespolitik; political parties; politiska partier; political leaders; politiska ledare; leisure time activities; fritidsaktiviteter; organizations; organisationer; reading (activity); läsande; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Religion and values; Religion och värderingar; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap